Diosmium compounds containing bis(imidazole)- p -quinone bridging ligands - Dhara, Suman; Ansari, Mohd Asif; Schwederski, Brigitte; Filippou, Vasileios; Kaim, Wolfgang; Lahiri, Goutam Kumar (Dalton transactions : an international journal of inorganic chemistry, 2022)
The doubly deprotonated bridging ligand L derived from 2,6-bis(2-pyridyl)-1,5-dihydro-1',4'-benzoquinono[2',3'- :5',6'- ']diimidazole H L forms coordination compounds with two bis(2,2'-bipyridine)osmium(II) complex fragments in ([1](ClO ) ) and configurations ([2](ClO ) ) of {(μ-L )[Os(bpy) ] }(ClO ) , as evident from crystal structure analyses. Exchange of the metal-coordinating 2-pyridyl functions in the bridge through non-coordinating 4-tolyl substituents (L → L ) leads to [3](ClO ) which involves chelation of the [Os(bpy) ] groups through imidazole-N and carbonyl-O atoms of the central -quinone function. In addition to identification, the compounds were subjected to electrochemical (CV, DPV) and spectroelectrochemical (UV-vis-NIR, EPR) analyses of electron transfer, the results being supported by results from TD-DFT calculations. Essential differences between [1 ]/[2 ] and [3 ] systems were found regarding variable but mostly metal centred oxidation, the two processes separated much more for [3 ]. The first reduction is bpy ([1 ], [2 ]) or quinone ligand centred ([3 ]). Electronic structures and electron transfer behaviour are thus highly sensitive to differences of configuration and coordination.